EFFECT OF LABOR GYMNASTICS TO DIMINISH THE FIRE BRIGADE PAIN THAT ARE DOING SERGEANT TRAINING COURSE (Fiep Bulletin - online, 2012)
The activities carried out bj fire brigade are dangerous and, so they can get sick [16]. What can we expect of a hard training season, which wake them physically and mentally too tired? On the other hand, labor gymnastics is an activity of physical exercises developed at workplace and one of its purpose is promoting health and preventing physical pain [17]. So, the aim of this paper is identifying and determing pain symptoms before and after applying a labor gymnastics program for fire brigade sergeant training course. It's an experimental study with quantitative approach regarding data analysis and 32 soldiers participated in it. It was used a methodology with an educational speech, the application of corlett's questionnaire and labor gymnastics form, this search was done during three months, for 10 minutes, three times a week. As result was possible to notice and concluding that the knees and spine are the most affected parts of the body and labor gymnastics proved to be good in diminishing all the pain. It was presented to institution as a preventive measure and its application was asked as part of other course routine.
Keywords: labor gymnastics; fire brigade; pain; prevention.